Biomarkers, isolation methods, and therapeutic implications of breast cancer stem cells - Teoh, Peik Lin; Nurshafiqah Saini (Elsevier B.V., 2025)
Breast cancer metastasis and relapse remain uncontrollable despite significant advancements in early diagnosis and treatment, resulting in increased mortality. Breast cancer is the most frequently diagnosed cancer in women worldwide and has become the leading cause of cancer-related deaths. Cancer stem cells (CSCs) may play significant roles in tumor initiation, maintenance, invasion, relapse, metastasis, and therapy resistance. Although this small, highly heterogeneous, and restricted population of CSCs has been extensively studied, their cellular and molecular physiology remains unclear. Nonetheless, CSCs have increasingly become an attractive therapeutic target for combating advanced, treatment-resistant cancers. This necessitates the development of effective and reliable methods for their isolation and enrichment. This review provides an overview of the key characteristics of breast cancer stem cells (BCSCs) and illustrates their role in therapeutic resistance. Furthermore, it highlights various mechanisms underlying cancer cell adaptability and therapy-induced resistance across different breast cancer subtypes. The commonly used methods for BCSC isolation and identification are also discussed, as they could facilitate a deeper understanding of tumorigenesis, metastasis, resistance, and relapse, consequently contributing to the development of more effective therapeutic strategies for breast cancer.